Economic evaluation on tight sandstone gas development projects in China and recommendation on fiscal and taxation support policies - Zhen Yang; Lingfeng Kong; Min Du; Chenhui Zhao (Natural Gas Industry B, 2016)
China is rich in tight sandstone gas resources (“tight gas” for short). For example, the Sulige Gasfield in the Ordos Basin and the Upper Triassic Xujiahe Fm gas reservoir in the Sichuan Basin are typical tight gas reservoirs. In the past decade, tight gas reserve and production both have increased rapidly in China, but tight gas reservoirs are always managed as conventional gas reservoirs without effective fiscal, taxation and policy supports. The potential of sustainable tight gas production increase is obviously restricted. The tight gas development projects represented by the Sulige Gasfield have failed to make profit for a long period, and especially tight gas production has presented a slight decline since 2015. In this paper, a new economic evaluation method was proposed for tight gas development projects. The new method was designed to verify the key parameters (e.g. production decline rate and single-well economic service life) depending on tight gas development and production characteristics, and perform the depreciation by using the production method. Furthermore, the possibility that the operation cost may rise due to pressure-boosting production and intermittent opening of gas wells is considered. The method was used for the tight gas development project of Sulige Gasfield, showing that its profit level is much lower than the enterprise's cost level of capital. In order to support a sustainable development of tight gas industry in China, it is recommended that relevant authorities issue value-added tax (VAT) refund policy as soon as possible. It is necessary to restore the non-resident gas gate price of the provinces where tight gas is produced to the fair and reasonable level in addition to the fiscal subsidy of CNY0.24/m3, or offer the fiscal subsidy of CNY0.32/m3 directly based on the on-going gate price. With these support policies, tax income is expected to rise directly, fiscal expenditure will not increase, and gas consumption cost in China will be significantly cut down.